Obstructive sleep apnea (OSA) and safety driving - Garbarino, Sergio (La Medicina del Lavoro, 2017)
Intermittent hypoxia and sleep fragmentation cause excessive daytime sleepiness (EDS) and cognitive impairment in obstructive sleep apnoea (OSA); neuroimaging and neurophysiological studies in patients with OSA have delineated a putative regional “fingerprint” of OSA-induced brain injury: a disconnection of the fronto-parietal regions and a disruption of the thalamocortical oscillator, with involvement of the hippocampal formation with impaired attention, awareness, working memory, time reaction, visuoconstructive and executive functions. For these reasons OSA is the main medical cause of EDS and is also associated with an increased risk of motor vehicle accidents (MVAs). About 7% of MVAs for a population of male drivers involved in MVAs are attributable to OSA. Subjects with OSA have nearly twofold increased odds of work accidents. Professional drivers add fatigue to sleep deprivation. A higher risk of MVAs cannot be adequately explained by OSA and sleep deprivation (SD), and EDS is a further, independent risk factor like the other two.  There is an association between the amount of hours of sleep per night and MVA or near miss accidents (NMA) rates with an inverse linear correlation.  When OSA, SD or EDS are present, the risk of MVAs or NMAs in truck drivers is severely increased. Taking a rest break or a nap appear to be protective against MVAs e NMAs and they should be considered a primary prevention strategy together with screening for OSA, EDS, and SD.